Biology of Spodoptera litura Fabricius (Lepidoptera: Noctuidae) on Artificial Feeds at Laboratory - CICI HARIYANTO PUTRI; SARBINO SARBINO; SRI RAHAYU (Fakultas Pertanian Universitas Tanjungpura, 2019)
Spodoptera litura (F) is one of the polyphagic pests. This study aims to determine the biological differences of S. litura (F) in artificial feed in the laboratory. The research was carried out in the laboratory of Plant Pest Faculty of Agriculture of Tanjungpura University from February - April. S. litura (F) is preserved in plastic cups (ice hood). The feed used was Phaseolus vulgaris L. and Vigna unguiculata L. The observations were made on 100 tails as individual cohorts per glass. The results of this study showed that Phaseolus vulgaris L. development period of S. litura (F) from hatching to imago ranged from 27 - 34 days, egg stage ranged from 3 - 9 days. The larvae consist of 5 instar, long instar stages I (2-3 days), instar II (4-6 days), instar III (2-4 days), instar IV (2 - 6 days), and instar V (1 - 4 days), pupa (5 - 12 days). The length of life of male imago ranges from 1 - 13 days and female imago 1 - 15 days. The post-spawning period ranges from 1 - 5 days. Fertility of eggs with an average of 84.08%. The number of eggs produced an average of 2,195.7 grains. In the feed Vigna unguiculata L. the developmental period of S. litura (F) from hatching to become imago ranged from 31 - 42 days, the stage of eggs ranged from 3 to 10 days. The larvae consist of 5 instar, long instar stages I (2-4 days), instar II (3 - 10 days), instar III (4 - 13 days), instar IV (3 - 11 days), and instar V (2 - 6 days), pupa (7 - 18 days). The length of life of the male imago ranges from 3 to 14 days and the female imago ranges from 2 - 17 days. Pre-breeding periods range from 3 - 9 days. The post-spawning period ranges from 1 to 6 days. Fertility of eggs an average of 77.06%. The number of eggs produced an average of 802.5 grains. Based on the average life cycle and the number of eggs produced then Phaseolus vulgaris L. can be recommended as feed for mass propagation.Keywords: Artificial Feed, Biology, Phaseolus vulgaris L., S. litura (F), Vigna unguiculata L.